Content Analysis of Organic Food Claims on Websites and Instagram Stores - Saraswati, Miranti Alfiah; Sumarwan, Ujang (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2021)
Organic food products are produced without pesticides or genetic engineering. This study analyses the variable product characteristics, website characteristics, Instagram account characteristics, and claims characteristics. This study aimed to analyze the content of claims for organic food on websites and Instagram stores based on the Consumer Protection Law No. 8 of 1999. This study used an exploratory design with content analysis methods. The sample was selected using purposive sampling, namely 100 online shops that sell organic food with details of 50 websites and 50 Instagram accounts. The data collected was categorized and processed using Microsoft Excel, Statistical Package for Social Science (SPSS) 23.0 and Nvivo 12 Plus. The analysis results show that 56% of website and Instagram stores use subjective claims and 40% using objective claims. As much as 47% of online stores, both websites and Instagram, are categorized as not misleading, and 53% are categorized as misleading or deceptive claims such as ambiguous. 22% of online shops violate Article 8 Paragraph 1, and 20% of online stores violate Article 9 of the Consumer Protection Law.